2008
DOI: 10.1016/j.tvjl.2007.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Animal noroviruses

Abstract: Among enteric caliciviruses, noroviruses belong to the genus Norovirus, one of the four accepted genera in the family Caliciviridae. These single-stranded, positive-sense RNA viruses are highly variable both genetically and antigenically. Several animal enteric caliciviruses that are morphologically indistinguishable and genetically closely related to human noroviruses have been identified. The first bovine enteric noroviruses were described in Great Britain and are known as Newbury Agent 2. At least three gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
93
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 160 publications
0
93
0
6
Order By: Relevance
“…The VTB for the specific detection of human and animal AdV and NoV specifically targets some of the most common human and animal enteric or respiratory viral pathogens (13,16,25,38,41) as well as Fϩ RNA bacteriophages, which are generally found as part of the normal gut flora of humans and animals (3). Once released into the environment, AdV, NoV, and Fϩ RNA bacteriophages are considered very stable in the environment and are found frequently in contaminated rivers, freshwater, marine water, groundwater, drinking water, and shellfish (4, 7, 10-12, 26, 27, 36, 39, 49).…”
Section: Discussionmentioning
confidence: 99%
“…The VTB for the specific detection of human and animal AdV and NoV specifically targets some of the most common human and animal enteric or respiratory viral pathogens (13,16,25,38,41) as well as Fϩ RNA bacteriophages, which are generally found as part of the normal gut flora of humans and animals (3). Once released into the environment, AdV, NoV, and Fϩ RNA bacteriophages are considered very stable in the environment and are found frequently in contaminated rivers, freshwater, marine water, groundwater, drinking water, and shellfish (4, 7, 10-12, 26, 27, 36, 39, 49).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the nucleotide sequence diversity of the ORF2, human NoVs are currently classified into five genogroups (GI-GV) (Clarke et al 2012;Green 2013). Human infection has been associated with genogroups I, II and IV while genogroups III and V infect cows and mice, respectively (Zheng et al 2006;Scipioni et al 2008;Clarke et al 2012). Porcine strains and a strain from lions are grouped in GII (Martella et al 2007) while a strain from a dog was identified in GIV (Martella et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The virus is highly contiguous, resistant to commercially used disinfectants, and has a low infectious dose (2,29,49). However, human NoV remains difficult to study because it cannot be grown in cell culture and it lacks a small-animal model (14,44). Furthermore, there is no vaccine or antiviral drug against this virus (33,47).…”
mentioning
confidence: 99%